2018
DOI: 10.1007/s00192-018-3703-6
|View full text |Cite
|
Sign up to set email alerts
|

Urolastic®, a new bulking agent for treatment of stress urinary incontinence: a systematic review and meta-analysis

Abstract: Urolastic® showed effectiveness in patients with SUI during a follow-up period of 6-24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It's unique feature is that it polymerizes in situ into a uniform elastomer, remaining flexible and adapting itself to the environment. This is thought to reduce the risk of migration . In a clinical trial in the Netherlands, 76‐88% of the patients showed subjective improvement at 12‐25 months follow‐up …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It's unique feature is that it polymerizes in situ into a uniform elastomer, remaining flexible and adapting itself to the environment. This is thought to reduce the risk of migration . In a clinical trial in the Netherlands, 76‐88% of the patients showed subjective improvement at 12‐25 months follow‐up …”
Section: Resultsmentioning
confidence: 99%
“…This is thought to reduce the risk of migration. 38,39 In a clinical trial in the Netherlands, 76-88% of the patients showed subjective improvement at 12-25 months follow-up. 40 In conclusion, although, there have been a number of studies conducted to look at the short-term efficacy, durability and safety of UBAs, in order to guide future practice, further comparative randomised trials involving a placebo or conservative treatment arm are required with long-term follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Currently marketed is a solid implant, Urolastic ® , which consists of a vinyldimethyl terminated polydimethylsiloxane polymer, tetrapropoxysilane cross-linking agent, platinum vinyltetramethyl siloxane complex catalyst and titanium dioxide radiopacifying agent 48. The material polymerizes in situ to form an elastomer, changing from a liquid to a solid state to form a cuff effect around the urethra 48. Urolastic ® is associated with vaginal erosion rates of up to 21.5%, many of which required implant excision 49…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these characteristics result in more durable cure rates as compared to the more hydrophilic bulking agents that tend to be absorbed over time. Single surgeon prospective cohort studies showed objective cure rates following PDMS-U varying from 33% up to 67% [8]. Overall complications of PDMS-U occurred in 24% of patients and included urinary retention, pain, haematuria, infection, urinary issues (frequency, urgency, incontinence), and erosion of the urethra/vaginal wall [9].…”
Section: Introductionmentioning
confidence: 99%